WAYS OF RISK MANAGEMENT IN PROTECTING THE ASSETS OF COMMERCIAL BANKS (Marketing Journal, 2025)
This article presents insights into risk management practices aimed at protecting the assets of commercial banks, with a focus on their application in Uzbekistanʼs national economy. It highlights measures taken during the financial sectorʼs systematic reform, including the development of competitive conditions and adoption of modern banking practices. The study also addresses challenges in applying international experience to local banking risk management and provides the authorʼs recommendations for improvement.
Keywords: commercial bank; banking risks; digital transformation; innovative banking; banking products; management structure; bank strategy; assets; liabilities; margin; credit; deposit; interest and non-interest income and expenses. 289